Crescimento da macrófita invasora Hedychium coronarium J. Köenig (Zingiberaceae) sob influência de agentes estressores e biomassa seca de Salvinia auriculata Aubl. - Moura, Vitória Fabri de (Universidade Federal de São Carlos, 2025)
Water pollution from stressors, such as emerging contaminants and agro-industrial waste, poses a challenge to aquatic ecology in urban-rural environments. These compounds alter biogeochemical cycles, affect plant communities, and can favor the growth of populations of invasive species that are more tolerant to stress. Although macrophytes play fundamental ecological roles, such as nutrient cycling and habitat provision, the uncontrolled growth of invasive macrophytes, such as Hedychium coronarium, suppresses native species and alters the structure of riparian ecosystems. This work is structured in three chapters. Chapter 1 presents an integrated review of water, macrophytes, biological invasion, and pollution, with emphasis on the effects of sodium dodecyl sulfate (SDS) and vinasse in aquatic environments, and the implications for biodiversity conservation. In Chapter 2, the population of H. coronarium in the Monjolinho reservoir (São Carlos, SP) was characterized using morphometric descriptors and biomass-volume relationships, which highlighted its plasticity and capacity to colonize degraded environments. Chapter 3 evaluated the growth of H. coronarium under controlled exposure to SDS (0.5 g L⁻¹ and 1.0 g L⁻¹) and vinasse (10% and 20%), both with and without dry biomass of Salvinia auriculata as mulch. DSS did not significantly reduce H. coronarium biomass compared to the control, but the presence of S. auriculata mulch altered growth responses, with a hormetic pattern. For vinasse, there was a significant reduction in H. coronarium biomass, and in the presence of S. auriculata mulch, biomass values remained close to those of the control. The results indicate that stressors exerted negative pressures on the growth of H. coronarium and that mulching with S. auriculata modified plant growth patterns under chemical stress conditions, demonstrating that pollutants alter the growth of this invasive species and that plant residues can interfere with the modes of action of these agents on macrophytes, with implications for management strategies and mitigation of impacts in aquatic ecosystems.
Growth of the invasive macrophyte Hedychium coronarium J. Köenig (Zingiberaceae) under the influence of stressors and dried biomass of Salvinia auriculata Aubl.
Keywords: Macrófitas aquáticas; Espécies invasoras; Contaminantes emergentes; Vinhaça; Bioensaios; Aquatic macrophytes; Vinasse; Invasive species; Emerging contaminants; Bioassays; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; 15. Vida Terrestre; 6. Água Potável e Saneamento